Global factory : foreign assembly in international trade - Grunwald, Joseph (Brookings Institution Washington DCUS, 1985)
Examines industrial collaboration between developed and developing countries focusing on the transfer of assembly operations abroad. Discusses internationalization of semiconductor industry by the USA, Western Europe, and Japan, and shows strengths and weaknesses of the various policy alternatives available in this industry. Presents case studies of assembly industries in Mexico, Haiti, and Colombia. Reviews the political, social, and economic effects of reorganization of industry abroad and summarizes policy implications for the USA and developing countries that are its partners.